To Determine the Effectiveness of Work Motivation, Through Communication Skills Training Program: A study of Medical Universities’ Teachers at Karachi (Medical Forum Monthly, 2024)
Objective: The purpose of this study was to determine the effectiveness of the teachers training program at Medical University of Karachi. The study also aims to identify the requirements of Medical teachers in attending the training program.Study Design: Case control studyPlace and Duration of Study: This study was conducted at the Department of Physiology, Baqai Medical University, Karachi from November 2015 to March 2015.Materials and method: Data accumulated through a set of questionnaire to that amount consists concerning twenty nine items. Sixty Medical instructors whoever attended the training program had been topics concerning the research.Results: The responses had been analyzed by way of using the “Statistical Package for Social Science” (SPSS) 16.0. Statistical evaluation used to be ancient to analyze the responses. The Overall Effectiveness was 0.001, Building Teacher Confidence <0.001 and improving teacher motivation was 0.030. Further, rests of the factors were found insignificant response.Conclusion: This component becomes the necessary needs over teachers because obeying the subsequent training program as observed by using the advantage about instructors that they want simple competencies have to stand addicted before long of the education program. The instructors additionally claimed they require the training program must stay longer (long term training) in light of the fact that it has demonstrated that the preparation was successful.